Life-cycle savings for a flat-plate solar water collector plant in Chile. (November 2017) - Araya, R.; Bustos, F.; Contreras, J.; Fuentes, A.
Abstract: In Chile, flate-plate solar water collector (FPSWC) plants have not yet been sufficiently developed despite the excellent solar conditions of the country's territory. Two of the main parameters affecting the behavior of these plants are the collection area and the water storage volume. In this paper, an energy performance model of an FPSWC plant is used along with genetic algorithms (GAs) to optimize the combination of these two parameters in order to produce the maximum life-cycle savings (LCS). This model is applied to 182 locations in Chile and 6 consumption profiles with the purpose of creating a solar map for this kind of plant throughout the country. The financial results show that the installation of an optimized FPSWC plant is convenient in all the analyzed locations. Furthermore, results are noteworthy in the northern zone of Chile with respect to the others due to excellent meteorological conditions. A sensitivity analysis was carried out at the locations with higher and lower LCS, showing that consumption temperature mainly affects zones with higher radiation. This study allows us to provide evidence that the utilization of FPSWC plants should be promoted in order to induce rapid growth and development of this important technology in Chile. Highlights: An evaluation methodology for flat-plate solar water collectors (FPSWC) plants is proposed. The potential of a FPSWC plant is evaluated for 182 locations in Chile. The Genetic Algorithm approach is applied to optimize the FPSWC plant. Water consumption and temperature profiles have a large impact on the FPSWC plant. The economic results show that for any locations a FPSWC plant is convenient.